Tilikan Filosofik tentang Konsep, Metodologi, dan Tujuan Pendidikan Islam - Hidayat, Yogi Fery (Tamadduna: Jurnal Peradaban, 2025)
Through a philosophical perspective on Islamic education, we can understand the essence of education in Islam and how education can shape human character and develop its potential holistically. This study aims to discuss the concepts, methodologies, and goals from the perspective of Islamic educational philosophy. The method used in this research is a qualitative approach through literature review and text analysis. The results of the study show that Islamic educational philosophy has a complex concept and broad goals, which include the development of character, morality, and ethics in Islamic education. The methodology of Islamic education is based on pedagogical principles derived from the verses of the Qur'an and hadith traditions, as well as Islamic intellectual traditions. This research also shows that Islamic educational philosophy can help create a civilized society through the development of strong character and morality within the community.